2018
DOI: 10.1074/mcp.ra117.000277
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Proteomic and Transcriptomic Analysis Reveals Long Noncoding RNA HOX Transcript Antisense Intergenic RNA (HOTAIR) Promotes Hepatocellular Carcinoma Cell Proliferation by Regulating Opioid Growth Factor Receptor (OGFr)

Abstract: Long noncoding RNA HOX transcript antisense RNA (HOTAIR) is involved in human tumorigenesis and is dysregulated in hepatocellular carcinoma (HCC). However, the molecular mechanisms underlying HOTAIR functions in HCC are largely unknown. Here, we employed an integrated transcriptomic and quantitative proteomic analysis to systematically explore the regulatory role of HOTAIR in HCC. A total of 673 transcripts and 293 proteins were found to be dysregulated after HOTAIR inhibition. Bioinformatics studies indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 79 publications
2
36
0
Order By: Relevance
“…Bioinformatics analysis and experiments in liver cells showed that HOTAIR activated by forkhead box C1 (FOXC1) promoted tumorigenesis of HCC in part through the modulation of miR‐1 . Integrated proteomic and transcriptomic screening, as well as subsequent functional assays, have also revealed that the effect of HOTAIR on cell proliferation can be partially mediated by the OGF‐OGFr axis and the downstream p16 INK4a and p21 W AF1/CIP1 pathways . These findings demonstrate that HOTAIR may act as a carcinogenic gene that influences tumor cell development …”
Section: Discussionmentioning
confidence: 93%
“…Bioinformatics analysis and experiments in liver cells showed that HOTAIR activated by forkhead box C1 (FOXC1) promoted tumorigenesis of HCC in part through the modulation of miR‐1 . Integrated proteomic and transcriptomic screening, as well as subsequent functional assays, have also revealed that the effect of HOTAIR on cell proliferation can be partially mediated by the OGF‐OGFr axis and the downstream p16 INK4a and p21 W AF1/CIP1 pathways . These findings demonstrate that HOTAIR may act as a carcinogenic gene that influences tumor cell development …”
Section: Discussionmentioning
confidence: 93%
“…HOTAIR also binds to transcripts and proteins. An integrated transcriptomic and quantitative proteomic analysis revealed that a total of 673 transcripts and 293 proteins are regulated by HOTAIR [ 121 ]. The analysis also showed that HOTAIR controls cell proliferation by regulating opioid growth factor receptor ( OGFR ) expression [ 121 ].…”
Section: Widespread Lncrna Dysregulation In Hccmentioning
confidence: 99%
“…The present study evaluated the relationship between HOTAIR and glucose metabolism in HCC cells [46]. In a recent study, HOTAIR stimulated HCC cell proliferation by regulating the opioid growth factor receptor, a negative biological regulator of cell proliferation [12]. Liver fibrosis is an active wound healing process that leads to portal hypertension and liver cirrhosis, resulting in HCC.…”
Section: Hotair In Hepatocellular Carcinomamentioning
confidence: 99%
“…HOTAIR can also alter gene expression at the post-transcriptional level by base pairing with translation factors or ribosomes to control translation or by binding to splicing factors to modulate splicing. Aberrantly increased HOTAIR expression has been detected in several tumors, and HOTAIR expression has been positively correlated with initiation, growth, angiogenesis, progression, drug resistance, recurrence, and poor prognosis by regulating several downstream targets via multiple signaling pathways in cancer [11][12][13][14][15] (Table 1). Polymorphisms of lncRNAs, including HOTAIR polymophisms, have been associated with the risk and susceptibility of the occurrence and development of human cancer; whether this is a potentially predictive and therapeutic biomarker remains undetermined [16][17][18][19][20].…”
Section: Reviewmentioning
confidence: 99%